Policing in England and Wales, 1918-39 - Laybourn, K. author. aut Link
XII, 256 p.
Keywords: An examination of the modernization of the English and Welsh police during the interwar years, focusing upon the increasing professionalization of the police, the Federation, forensic work and the growth of traffic policing. The authors challenge the established viewpoint by arguing that this period saw significant changes in policing.